Maternal Health Disparities across Pregnancy Complications, Death Rates, and Causes - Khatak, Kalsoom Habib; Younus, Mohammad Imran; Ikram Ullah, (Indus Journal of Bioscience Research, 2025)
This study investigates maternal health outcomes in Dir Lower District, focusing on complications during pregnancy and delivery across three maternity settings: government hospitals, private clinics, and home-based deliveries, from 2023 to March 2025. The aim is to identify and compare the incidence of complications, death rates, age distribution, and the causes of maternal deaths across these different delivery settings. This report presents an analysis of 47 maternal deaths, with 23 cases involving complications during pregnancy and delivery and 24 without. The distribution of deaths by facility type shows 35 deaths in government facilities, 40 in home-based settings, and 36 in private facilities. Causes of death include anemia (19 deaths), ectopic pregnancy (17 deaths), hypertensive disorders (9 deaths), infections (16 deaths), obstetric hemorrhage (6 deaths), obstructed labour (4 deaths), and sepsis (11 deaths). Regionally, 36 deaths occurred in rural areas and 11 in urban areas. The age distribution of deceased women spans from 15 to 50 years, with notable concentrations at ages 15, 23, 44, and 47. These findings provide a comprehensive overview of maternal mortality across various factors including complications, facility type, causes of death, and age distribution.